Schistosomiasis Among Female Migrants in Non-endemic Countries: Neglected Among the Neglected? A Pilot Study - Roure, Sílvia; Pérez-Quílez, Olga; Vallès, Xavier; Valerio, Lluís; López-Muñoz, Israel; Soldevila, Laura; Torrella, Ariadna; Fernández-Rivas, Gema; Chamorro, Anna; Clotet, Bonaventura (Frontiers in Public Health, 2022)
Background Schistosomiasis among migrant populations in Europe is an underdiagnosed infection, yet delayed treatment may have serious long-term consequences. In this study we aimed to characterize the clinical manifestations of Schistosoma infection among migrant women, and the degree of underdiagnosis. Methods We carried out a prospective cross-sectional study among a migrant population living in the North Metropolitan Barcelona area and coming from schistosomiasis-endemic countries. We obtained clinical, laboratory and socio-demographic data from electronic clinical records, as well as information about years of residence and previous attendance at health services. Blood sample was obtained and schistosomiasis exposure was assessed using a specific ELISA serological test. Results Four hundred and five patients from schistosomiasis-endemic regions were screened, of whom 51 (12.6%) were female. Seropositivity prevalence was 54.8%, but considering women alone we found a prevalence of 58.8% (30 out of 51). The median age of the 51 women was 41.0 years [IQR (35–48)] and the median period of residence in the European Union was 13 years [IQR (10–16)]. Schistosoma-positive women (N = 30) showed a higher prevalence of gynecological signs and symptoms compared to the seronegative women (96.4 vs. 66.6%, p = 0.005). Among seropositive women, the median number of visits to Sexual and Reproductive Health unit prior to diagnosis of schistosomiasis was 41 [IQR (18–65)]. Conclusion The high prevalence of signs and symptoms among seropositive women and number of previous visits suggest a high rate of underdiagnosis and/or delayed diagnosis of Schistosoma infection, particularly female genital schistosomiasis, among migrant females.